Capital Structure and Firm Growth: R&D Intensive Companies - Salminen, Jussi (My University, 2013)
The purpose of this study is to examine and explain firm`s growth impact on capital structure decision-making in research and development intensive companies. Many studies claim that R&D has a pivotal impact on capital structure decisions, but corporate finance theories have often failed to explain these observed patterns. As sales growth is an important concept and objective for R&D firms, it is logical to assume that it plays a vital role in capital structure decisions. This study applies nomothetic research approach. The theoretical part employs a formal conceptual analysis in order to develop the propositions that are tested with empirical data. The empirical part consists of the analysis of three companies; the data is obtained from the annual reports over the period 2003 – 2008. The companies operate in IT- or ICT-industry and are publicly listed. The method for analyzing the case data is based on the financial indicators, which are obtained from the financials of the case companies. These economic indicators describe the capital structure and the financial decision-making of the firms. The method relates to the quantitative studies. Yet, this study extends the analysis beyond the indicators. Specifically, this study addresses the question of what is behind the economic indicators, therefore combining aspects of quantitative and qualitative analysis. The firms examined in this study seem to prefer internal finance during growth. However, external finance seems to be a catalyst for sales growth. Firms strongly prefer equity financing. In growth, the use of equity per capital either increases or stays in a constant level. Over the period 2003 – 2008, the firms were often associated to equity related transactions and short-term debt. Short-term debt was used as a substitute of long-term debt and equity. The case firms also adjusted their capital structure – these adjustments were carried out with short-term debt or equity. The case data also provides implications for the growth signal theory that was developed in this study. Based on the econometric indicators, arguments can be made that equity investors are `attracted` to growing R&D firms. This is because growth helps investors perceive the true type of firm. The findings of this study are best explained by the trade-off theory and the pecking order theory. These corporate finance theories are considered as mainstream. Little support can be found to the implications of the signaling theory and market timing theory.